An investigation report about the lack of VB1 - Zhu, Hangju; Sun, Guiju; Zhu, Baoli (Journal of Thoracic Disease, 2016)
From August 1 to September 26, 2012, 30 workers who had the symptom of edema in both lower limbs were reported in Yancheng, Four severe edemas in both lower limbs workers were sent to the hospital, and one person of the workers died. The epidemiology investigation and laboratory testing (in the urine loading tests, the concentration of VB1 of the workers living in the factory for more than half of the year decreased far below the normal values) were conducted to explore the cause. Furthermore, after one-week intramuscular injection of thiamine treatment, the clinical symptoms of the workers had been improved greatly. Finally, the lake of the thiamine (VB1) was considered to be the reason of this incident.